2014
DOI: 10.7763/ijcea.2014.v5.396
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Absorption of CO2 into Aqueous Mixtures of Methyldiethanolamine and Diethanolamine

Abstract: Abstract-The effect of mixing a tertiary amine, N,N-Methyldiethanolamine (MDEA), with a secondary amine, diethanolamine (DEA), on the kinetics of the reaction with carbon dioxide in aqueous media has been studied in a stirred cell reactor with a plane, horizontal gas-liquid interface. Temperature was varied from 293 to 313K over a range of blend composition and total mixture concentration ranging from one to two molars. The proposed model representing the reaction of CO 2 with the blends studied is found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Blended aminic absorbents containing MDEA have seen growing interest because they can combine the desirable properties of the individual components, in particular the high rate of reaction of the primary or secondary amine and the low enthalpy of reaction of the tertiary amine; for example, MEA/MDEA or DEA (diethanolamine)/MDEA mixed absorbents have been studied. In these cases, primary or secondary amine concentration compared to MDEA concentration has to be quite high to have a notable enhancement in the CO 2 absorption rate.…”
Section: Introductionmentioning
confidence: 99%
“…Blended aminic absorbents containing MDEA have seen growing interest because they can combine the desirable properties of the individual components, in particular the high rate of reaction of the primary or secondary amine and the low enthalpy of reaction of the tertiary amine; for example, MEA/MDEA or DEA (diethanolamine)/MDEA mixed absorbents have been studied. In these cases, primary or secondary amine concentration compared to MDEA concentration has to be quite high to have a notable enhancement in the CO 2 absorption rate.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the observed reaction order, Kumar et al 12 reported the reaction order for potassium salts to be in the range of 1 to 1.5 at 285 to 305 K. This high reaction order observed for both KTau and KGly in blended solutions indicates the effect of multiple bases in the deprotonation of the zwitterion. 34 Hence, the observed experimental pseudo-first-order rate constants were then analyzed using both the zwitterion and termolecular mechanisms.…”
Section: Methodsmentioning
confidence: 99%
“…The promoting effect of L-Arginine investigated in this work was also compared with that of the available data of MDEA-Glycine [42] and MDEA-DEA [58] systems at different temperatures and at the same overall concentration (1 M) as shown in Figure 13. For all three compared systems, the same 0.1 M of the promoter was added.…”
Section: Comparison Of the Promoting Effect Of L-argininementioning
confidence: 99%